Chinese Lantern-Type Stability Loss of Circular Piezoelectric Cylinder Under Unidirectional Pressure - Yesil, U. B.; Aylikci, F.; Yahnioglu, N. (SPRINGER, 2025)
The problem of Chinese lantern-type stability loss is studied for a circular cylinder made of piezoelectric (PZT) material subjected to uniformly distributed axial external pressure. Mathematical model is made within the framework of the exact three-dimensional equations of the nonlinear electro-elasticity theory. The infinitesimal imperfection criterion is used to determine the critical parameters. According to this criterion, the force that causes the amplitudes of the initial imperfection curves of the cylinder to increase indefinitely is accepted as the critical force. The solution of this problem is reduced to the solutions of the series boundary value problems. The critical parameters sought are determined by solving only the first two boundary problems (namely, the zeroth and the first approximations). The solution for the zeroth approximation is determined analytically. The first approximation is obtained numerically by using the finite element method. The effects of various geometric and material parameters as well as a coupling between electrical and mechanical fields on the stability loss of PZT cylinder are investigated.
Keywords: piezoelectric cylinder; stability loss; finite element method; PLATE; Mechanics